Gendered Confidence in EFL Presentations: Analysing Gender Differences and Learning Capabilities - Irsyam Surahim; Yayuk Christianti; Budiarti Putri Uleng (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Oral presentations are an important activity in language learning because they provide students with the opportunity to develop communication skills, convey ideas effectively, and interact meaningfully. This study used a qualitative approach to gain an in-depth understanding of students' experiences during presentations. The purpose of this study was to analyze the influence of gender differences on students' confidence levels in making oral presentations in English as a Foreign Language (EFL) learning. Data were collected through classroom observations, semi-structured interviews, and document analysis. The participants consisted of male and female students taking an english speaking skills course. Data analysis was conducted using thematic analysis techniques. The results showed that male students tended to display higher confidence in speaking spontaneously and answering audience questions, while female students showed more thorough preparation, better mastery of the material, and more structured delivery. Factors influencing confidence included English language proficiency, presentation preparation, previous speaking experience, and classroom support. In addition, learning capability was shown to have a close relationship with presentation performance and students' confidence levels. This study emphasizes the importance of a supportive learning environment to increase active participation and reduce speaking anxiety in students regardless of gender.